The stances of e-government policies, processes and technologies - Kumar, Puneet; Pareek, Kumar Sambhav; Jain, Vinod Kumar (A Chapman & Hall Book, 2019)
"This book focuses on the three inevitable facets of e-government, namely policies, processes and technologies. The policies discusses the genesis and revitalization of government policies; processes talks about ongoing e-government practices across developing countries; technology reveals the inclusion of novel technologies"...